Littoral macroinvertebrates in lakes : patterns of distribution and potential use in ecological assessment - White, Jonathan (Trinity College (Dublin, Ireland). Department of Zoology, 2001)
The forthcoming European Council Directive establishing a framework on water policy will require Member States to monitor the ecological status of lakes. Biotic as well as physicochemical criteria must be included in monitoring programs. Benthic macroinvertebrates are used in river assessment as their distributions are influenced by biotic and abiotic factors including anthropogenic impacts. These factors and simple sampling procedures make them potentially useful for lake assessment. This work aimed to assess this potential, while taking into account natural spatial and temporal variability in macroinvertebrate distributions.
Keywords: Ecology, Ph.D.; Ph.D. Trinity College Dublin